Cage position and density effect on some welfare criteria in Denizli chicken - FIDAN, EVRIM DERELI; NAZLIGÜL, AHMET (The Indian Journal of Animal Sciences, 2013)
In this experiment, the effect of cage position (tier level) and cage density on some welfare criteria in Denizli Chickens were investigated. In the experiment, 252 hens were allocated to California type battery cages per partition (48×41×46 cm) systematically to from cage density (3, 4 and 5 hen/cage partition) and cage position (top, middle and bottom tier level) groups. The birds were housed 3, 4 and 5 birds / cage partition which resulted in 656.0, 492.0 and 393.6 cm2 of cage floor surface area/hen, respectively. Feed and water were provided ad lib. As a result of this study, Denizli fowls, differences between foot health and claw length values among cage density groups were found statistically significant. Feather degree was the highest in 3 bird density group (16.59 score) and the lowest in 5 bird density group (8.40 score). In the experiment, it was observed that the effects of cage density and cage position on heterophil lymphocyte ratio (h/l) were not significant.